Deciphering the core seed endo-bacteriome of the highland barley in Tibet plateau - Hao, Zhao; Wang, Yanhong; Guo, Xiaofang; De, Ji (Frontiers in Plant Science, 2022)
Highland barley (Hordeum vulgare var. nudum (L.) Hook.f., qingke) has unique physical and chemical properties and good potential for industrial applications. As the only crop that can be grown at high altitudes of 4200–4500 m, qingke is well adapted to extreme habitats at high altitudes. In this study, we analysed the seed bacterial community of 58 genotypes of qingke grown in different regions of Tibet, including qingke landraces, modern cultivars, and winter barley varieties, and characterised endophytic bacterial communities in seeds from different sources and the core endo-bacteriome of qingke. This study aim to provide a reference for the application of seed endophytes as biological inoculants for sustainable agricultural production and for considering microbe-plant interactions in breeding strategies. A total of 174 qingke seed samples from five main agricultural regions in Tibet were collected and subjected to investigation of endophytic endo-bacteriome using high-throughput sequencing and bioinformatics approaches. The phyla of endophytic bacteria in qingke seeds from different sources were similar; however, the relative proportions of each phylum were different. Different environmental conditions, growth strategies, and modern breeding processes have significantly changed the community structure of endophytic bacteria in seeds, among which the growth strategy has a greater impact on the diversity of endophytic bacteria in seeds. Seeds from different sources have conserved beneficial core endo-bacteriome. The core endo-bacteriome of qingke seeds dominated by Enterobacteriaceae may maintain qingke growth by promoting plant growth and assisting plants in resisting pests and diseases. This study reveals the core endo-bacteriome of qingke seeds and provides a basis for exploiting the endophytic endo-bacteriome of qingke seeds.